Nomenclature revision and validation of some syntaxon names of the orophilous vegetation in Greece - Tavilla, Gianmarco (Hacquetia, 2025)
This paper presents a nomenclatural revision and validation of some Greek syntaxa. These syntaxa occur on the summits of the highest mountains in mainland Greece, as well as on several Ionian (Lefkas, Cephalonia) and Aegean islands (Euboea, Samos, Lesvos, Chios, and Thassos). This revision was performed in accordance with the articles of the 4th edition of the International Code of Phytosociological Nomenclature. This work resulted in the validation and revision of 66 new syntaxa, the correction of 6 names (nomina correcta), the change of 1 name (nomen mutatum), and the designation of 11 lectotype. These nomenclature revisions pertain to the orophilous cushion-like vegetation of central-southern and insular Greece. Consequently, these findings address and resolve several nomenclatural issues previously existing in the syntaxonomy of Greece’s orophilous vegetation.